Deportation, Memory and the Self in Dalia Grinkevičiūtė’s Memoirs A Stolen Youth, A Stolen Homeland and Lithuanians by the Laptev Sea - Raskauskiene, Audrone (European Journal of Life Writing, 2014)
The present discussion adresses the issue of deportation, displacement, memory and the self in Dalia Grinkevičiūtė’s Lietuviai prie Laptevų jūros: Atsiminimai, miniatiūros, laiškai, written in 1949–50, first published in 1997 and in 2002 translated as A Stolen Youth, a Stolen Homeland, and in the second version of the memoirs, Lietuviai prie Laptevų jūros, written in 1974, in 1990 translated as Lithuanians by the Laptev Sea. At the age of fourteen, Dalia Grinkevičiūtė (1927-1987) was deported from Lithuania to Siberia during the mass deportations of 1941 and spent almost 10 years in Yakut Republic. Considering Grinkevičiūtė’s life experience writing memoirs may be understood as a means of composing or re-creating the self. At the same time, this re-creating of the self through narrative becomes a healing process to that wounded by the tragic experiences of deportation and exile. If we refer to Lacan, relating self to the others brings a healing effect. According to such scholars as Kohut, Hartmann, Modell, and Kernberg, a sense of self depends on the negotiations of self defined against and in relation to others, where the “other” takes the form of an object of various emotions. For many of these scholars, creativity, especially writing, performs the function of restoring or re-creating a sense of self and re-negotiating self-object relations. The idea of writing as re-creation of the self, can be related to autobiographical writing where this is quite explicit.